Bubble Burst vs. Defused Bubble: A Humble Opinion for When You are Sick - Gupta, Deepak (Indian Journal of Community Health, 2014)
When you are sick, all hell breaks loose. Solutions have problems and society may not have all the answers. When you are sick, you (or your society) may choose one of the many options for helping you override the tide of sickness. Basically four scenarios can reflect all types of healthcare. The best scenario can be that you can try age-old understanding of living life simpler and healthier in terms of quality of life. Quantity of life is secondary to the primary goal of quality of life. You should develop resilience in resisting the covert assaults of modifiable risk factors. Health promotion and disease prevention should be allowed to replace the currently overenthusiastic culture towards curing diseases. The health care is like a multifaceted (multipronged and non-spherical) balloon. This multipronged healthcare balloon will never be air-less but at least we can aim to achieve that only air-left (compressed air energy) inside the balloon are the catastrophes that are not made by us and hence, out of an individual’s direct control.